ANALISIS KETERKAITAN ANTARSEKTOR EKONOMI DI KABUPATEN TEBO PROVINSI JAMBI - , Himawan Susanto; , Dr. Soeratno, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to see the linkages between economic sectors and to determine the impact of final demand on the economy of Tebo district. The results of this study will be used to plan development in Tebo district. The Data used are secondary data, mainly from Input Output tables Tebo district in 2005 obtained from Bappeda of Tebo district. The problems in this study were analyzed with the Input Output model. This study showed that the palm oil sector has strong backward linkages with other sectors with the assumption that all sectors have added value. Sawmill and processing industries sectors have strong forward linkages. Residential building and non-residential building sector can improve higher peopleâs income, and the sectors belonging to the group of main employment as agricultural, forestry, hunting and fishing are able to absorb labor highest. Palm oil sector can also be used as alternatives to spur economic growth, increasing incomes and open up wider employment opportunities in Tebo district.